Jokes for All the Family - Hilton, Harry (London Summersdale, 2012)
Did you hear about the schoolboy who put clean socks on every day? By Friday he couldn't get his shoes on. Prepare to have your ribs tickled, your funny bone waggled and your leg pulled with this bumper compendium of jokes for all the family. With everything from ludicrous lions to preposterous pirates, there are laughs aplenty for everyone!
Includes Illustrations.
Keywords: English wit and humor